Effects of N-acetylcysteine on oxidative stress, interleukin-2, and running time in sedentary men - D. Leelarungrayub (2018)
Aim. The aim of this study was to evaluate the effects of short-term N-acetylcysteine (NAC) supplementation on oxidative stress, interleukin-2 (IL-2), and running time. Methods. Twenty nine men participated in this 7-day study. Six hundred mg of NAC was administered twice daily. Short exercise with heavy intensity (85% of MHR) was performed on a treadmill, before and after the 7 days and total running time until reaching 85% of MHR was recorded. Blood was tested for malondialdehyde (MDA), nitric oxide (NO), total antioxidant capacity (TAC), IL-2 and glutathione (GSH) before and 20 min after stop exercise either before or after supplemented. Results. At baseline, there were no significant difference in the baseline values of the dependent variables measured; whereas, after short exercise, the levels of GSH and TAC reduced and MDA and NO increased significantly in both groups. After 7 days, the pre-exercise levels of all parameters were not different, except for TAC and NO in the supplement group, were significantly higher than in the control. After exercise, TAC, MDA, and NO did not change significantly in the supplement group, but changed significantly in the control. GSH decreased significantly in both groups. IL-2 increased significantly in the supplement group after exercise, but decreased in the control group. Running time in both groups did not increase. Conclusion. It can be concluded that supplementing the NAC at 1,200 mg daily helps to control the oxidative stress and also activates specific IL-2 release from short heavy exercise.